2007
DOI: 10.1002/ijc.22334
|View full text |Cite
|
Sign up to set email alerts
|

Association of immunoescape mechanisms with Epstein‐Barr virus infection in nasopharyngeal carcinoma

Abstract: We have investigated the association of immunoescape mechanisms in nasopharyngeal carcinoma (NPC) lesions with EpsteinBarr virus (EBV) infection and clinical course of the disease. Tumor biopsy specimens obtained from 36 Japanese NPC patients were examined for antigen processing machinery component and HLA class I antigen expression, CD81 T cell infiltration, and Fas, Fas ligand (FasL) and IL-10 expression using immunohistochemical staining. The results were correlated with the histopathological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
(50 reference statements)
1
30
2
1
Order By: Relevance
“…One report in 2007 showed that the HLA class I antigen expression was significantly lower in stages III and IV patients compared to that of stages I and II NPC patients. 25 Our results were not consistent with this observation maybe due to most of our patients were in stages III and IV (82%, 46/56).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…One report in 2007 showed that the HLA class I antigen expression was significantly lower in stages III and IV patients compared to that of stages I and II NPC patients. 25 Our results were not consistent with this observation maybe due to most of our patients were in stages III and IV (82%, 46/56).…”
Section: Discussioncontrasting
confidence: 70%
“…While, other reports also found that EBV infection of NPC tumor cells could downregulate HLA class I antigen expression compared to EBV negative benign nasopharyngeal epithelial. 25 However, it has also been demonstrated that EBV positive NPC tumor cells could be recognized by autologous EBV specific CTLs in vitro; and the antigen proceeding and presenting system is intact in NPC tumor cell lines in previous research. 60,61 These founding provide the possibility of success for immunotherapy in some NPC patients who have intact antigen proceeding and presenting systems in tumor cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It plays a central role in the physiologic regulation of programmed cell death and has been implicated in the pathogenesis of various malignancies and diseases of the immune system. Fas ligand overexpression is an unfavorable prognostic marker in NPC (46,47).…”
Section: The Inferred Npc Network Consists Of Highly Interactive Cliqmentioning
confidence: 99%
“…Clinical studies with nasopharyngeal carcinoma (NPC) lesions during EBV infection suggest that LMP2, TAP1, tapasin and HLA class I antigens are downregulated [105].…”
Section: Regulation Of Tap and Tapasinmentioning
confidence: 99%